DIFFERENTIAL DIAGNOSIS OF HEARING IMPAIRMENTS BY MEANS OF A NEW ANALYSIS METHOD OF SPEECH DISCRIMINATION ABILITY - HOSOI, HIROSHI (Nippon Jibi Inkoka Gakkai Kaiho, 1984)
The relationship between the speech discrimination ability and the location of the organic lesion was investigated for hearing impaired patients by using a newly proposed index named "speech congnitive ability index". This index represents a part of the abnormality of the speech discrimination score, which cannot be accounted for by the damaged pure tone sensitivity measured by the pure tone audiometry. And this index was calculated as a normalized distance of a speech discrimination score from a normal standard. The normal standard was obtained from speech discrimination scores of normal hearing subjects for speech sounds filtered through an PIR digital filter which approximates the patient's pure tone audiogram, and represents the amount of the effect of the damaged pure tone sensitivity upon the speech discrimination ability. Then using this method as the theoretical background, a micro-computer system was developed to assess the speech discrimination ability of hearing impaired patients in consideration of their pure tone audiograms. The system was made so as to analyze how a patient fails to perceive speech sounds. Using this system, it was found that there is a tendency that the speech cognitive ability indices for patients with retrocochlear hearing impairments are lower than those for subjects with conductive or inner ear hearing impairments. And also, it was found that the way of confusion in speech perception caused by patients with retrocochlear hearing impairments is different from that caused by subjects with conductive or inner ear hearing impairments. Subsequently it was shown that this method is clinically applicable in estimating the locus of the lesion for patients with hearing impairments. Finally using this method, organic lesion of patients who have audiograms of so called sharp cut configulation is estimated in inner ear.